A Review on the Development of oil Palm, Pineapple and tea Leaves as Adsorbent for Arsenic, Zinc, Aluminium and Mangenese Removal From Wastewater - MOHD FOUZI, SAIDATUL HUSNA; OTHMAN, NORZILA (Recent Trends in Civil Engineering and Built Environment, 2021)
This paper was to determine the source of heavy metal in wastewater and the effect on health also elucidate the characteristics of leaves as activated carbon and the potential on heavy metal removal. This review paper used Scopus to find previous study that related to topic area. and the documents will be export to VOSViewer to get the visualization on the leaves waste as activated carbon. The application of leaves waste in removing heavy metal such as arsenic, manganese, zinc and aluminum from wastewater as activated carbon had been widely used. Leaves waste which is one of the wastes of agricultural, are abundantly accessible since there is a high agricultural activity. Example of leaves waste are oil palm, pineapple and tea leaves waste. The activated carbon will be analyze as stated in the previous study such as Fourier Transform Infrared Spectroscopy (FTIR) spectra result, Field Emission Scanning Electron Microscopy (FESEM) and Thermogravimetric Analysis (TGA). To produce activated carbon there are two ways, which is physical activation and chemical activation. In this review paper, the most leaves waste and heavy metal that had been found is tea waste and zinc, respectively. Overall, leaves waste can be suggested to be used as activated carbon in the elimination of heavy metals from industrial wastewater.